Patients’ Perception towards General and Pelvic Examination by Male Medical Students: A Cross-sectional Study in a Multi-ethnic Population - Thirunavuk Arasoo, Valliammai Jayanthi; Dominic , Nisha Angela; Ratnasingam, Vanassa; Ul Islam , Md Inzamum; Lee, Erin Ziyi; Wong, Jasmine Jia Min; Kong, Florence Wan Yiin; Himashi Pemasiri , Walimuni Devage Rashmi; Jeganathan, Ravichandran; Ramadas, Amutha (IIUM Medical Journal Malaysia, 2021)
Introduction Male medical students globally have difficulty in obtaining consent to perform pelvic examination. We sought to identify independent factors influencing women consenting to male medical students performing general and pelvic examination under supervision. Methods This cross-sectional study conducted at a tertiary hospital and a public health care centre in Johor Bahru, Malaysia recruited 369 women above 18 years old who have had sexual intercourse before and no prior hysterectomy. A validated self-administered bilingual questionnaire was used to collect data on factors that influence them consenting to male medical students examining them and performing pelvic examination when indicated. Results The respondents were largely below 30 years old (52.9%), Malays (73.4%) and Muslims (75.3%). The consent rates for general and pelvic examination were 27.4% and 18.9%, respectively. Being a Muslim, having an occupation and being introduced by a male medical specialist increased the likelihood of women consenting to general examination. However, a history of being examined by male students decreased the likelihood by 64%. Believing that male doctors should have the skills to treat patients in women's health was the only independent factor that increased the likelihood for women to consent for pelvic examination to be conducted by male medical students. Conclusion Believing that male doctors should be skilled in treating women positively influences decision to consent. Explaining earnestly to women on how they aid in developing the skills of future doctors should be prioritised. Keywords: patients’ perception; male medical students; pelvic examination